AGRICULTURE, HORTICULTURE IN HEVES COUNTY - Kaprinyák, Tünde (Acta Carolus Robertus, 2021)
With the spread of urbanization, the healthy nutrition, of which agriculture is an important basis, is becoming more and more important for people. There is an increasing emphasis on domestically produced plant „raw materials”. Among them, there are some plants, the formation and cultivation are connected to only one-one growing region. These areas also play a role in preserving genetic variability. The negative environmental impacts caused by climate change are also causing severe damage in the temperate zone. The growing areas are shifting, new pathogens and pests are able to find their habitat there. A possible solution could be to reintroduce domestic, historical varieties into cultivation again. Among the Hungaricums more and more domestic plant products can be found. The broadening the biological and genetic bases of species, the preserving tradition, is as important as the horticultural innovation. Due to the diverse geographical features of Heves county, the tradition of agriculture (including horticulture) dates back a long time. For many people living here, the growing of fruits and vegetables and related tourism also provide a livelihood.